Genesis of the right to legal assistance - Коршенко, Анна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The historical aspects of the formation and development of the right to legal assistance are analyzed in thearticle. The regularities and features of emergence the right to legal assistance at different historical stages indifferent nations of the world – in ancient Rome and Greece, the Kievan Rus, the Lithuanian-Russian era, theJudicial Reform in 1864 and to the period of Ukraine as an independent state are examined. Some aspects ofthe history of the advocacy as an important legal institution for providing the human right to legal assistanceare examined.